Hospital pharmacist challenges in evaluation of scientific evidence and its incorporation to pharmacotherapeutic protocols through therapeutic committees in COVID-19 times - Cecilia M. Fernández-Llamazares; Eduardo López-Briz (Farmacia Hospitalaria)
Type 2 coronavirus pandemics that is plaguing almost all the world has caused qualitative and quantitative strains in health systems that have had to be responded to. The lack of known vaccines and effective treatments has generated the need to use drugs with very little evidence for their incorporation into pharmacotherapeutic protocols agreed by the clinical team. The hospital pharmacist, within the multidisciplinary team, has been responsible for critically evaluating the alternatives and positioning them in these protocols. Finally, some ethical and legal questions that should be considered in this scenario are analyzed in this article.